Influence of monomer concentration on the morphology, contact angle, water uptake, and antibacterial activity of grafted cellulose obtained from peel durian - ROSLIANA LUBIS; SAISA SAISA (Universitas Syiah Kuala, 2022)
The objective of the current study is to evaluate and determine the effect of monomer concentration of ClAETA on the grafting copolymerization of oxidized cellulose which isolated from peel durian. Four concentrations of ClAETA were used in this study, e.g., 40, 50, 60, and 70%. Several analyses were performed to determine the material characteristic, e.g., degree of grafting, FT-IR, surface morphology, contact angle, degree of swelling, and antibacterial activity. The result showed, monomer concetration plays a significant role to the physical and surface morphology of DAC-ClAETA. The degree of grafting of ClAETA was found in the range of 15-31%, and at the concentration of 50% the grafted oxidized cellulose has 30.4% of degree of grafting. SEM images showed the pore volume has linear correlation to the monomer concetration, it increased the surface roughness. Also, the contact angle confirmed the hydrophilicity and degree of swelling of grafted oxidized cellulose was increase that linear to ClAETA concentration. DAC-g- ClAETA was found antibacterial active against S. aureus, S. epidermis, and C. albicans than DAC.